Para lembrar que você existe : um estudo de caso sobre as políticas de inclusão para os estudantes com deficiência na Universidade Federal do Espírito Santo - Sousa, Haila Lopes de (2013)
This work aims at analyzing the inclusion of deficient students into the Federal University of Espírito Santo (UFES), emphasizing the relationship between the policies proposed by the institution and the academic experience of the students who have deficiency. Nowadays there are serious researches about the inclusion of deficient students in college, but there is still a long way ahead (BUENO, 2002; MOREIRA, 2004; OLIVEIRA, 2007; CASTRO, 2011). The work has the characteristic of study case, in order to fulfill its goals (LUDKE; ANDRÉ, 1996). The theory of index paradigm with the support of writings by Ginzburg (2001) was used to help the understanding of the case. The author emphasizes the deficient students speeches so that it is possible to recognize the kind of treatment they receive inside the university. It also has the contribution of the cultural historical theory of Vigotski (1993) which thinks the subject based on its own view. The tool used to collect data was the documentary analysis as well as the semi-structured interview. It analyzes the education in Brazil from a historical perspective and observes how much the Brazilian education has suffered along the centuries. This is not different when we deal with university teaching. The interview was made with eleven students who belong to the deficient students files at UFES; they indicated some professors to be interviewed. Five of them answered the researcher s questions. Three managers of the University also participated in the research. They offered the official documents of UFES for analysis. Based on its data, the research makes it possible to see that the access to the University by means of the Entrance Examination is pointed out as something positive, since it enables the candidate, providing the necessary resources to do the test. It is also possible to observe that the financial help policies are well evaluated, but the students with deficiency believe that the question of help is not only that. It was also noticed that there is lack of accessible infrastructure, academic follow up, as well as school material for the students. There is also the necessity of giving the right direction to the professors work. It also shows the necessity of institutionalized policies for UFES.